Location of foreign firms in Portugal: A network approach - Jose Freitas Santos (European Regional Science Association (ERSA), 1998)
The importance of the Foreign Direct Investment (FDI) and the foreign firm in the portuguese economy has been rising quite significantly for the last years. Nevertheless, we might say that there has been little work which brings into focus the factors that provide us with a consistent explanation about the location of the foreign manufacturing firm. The paper try to clear up the above mentioned issue, considering an analytical framework that integrates the network approach. In this framework the social, intra-entrepreneurial, inter-entrepreneurial (both national and local) and the local institutional networks are supposed to exert a relevant influence on the location decision making process of the foreign manufacturing firm.
Keywords: 330